Actions, attitudes and beliefs of occupants in managing dampness in buildings. Issue 1 (1st October 2018) - Blay, Karen; Agyekum, Kofi; Opoku, Alex
Abstract : Purpose: Dampness in buildings affects the health of occupants, structural stability and energy efficiency of buildings. Solutions to managing dampness focus on promoting the use of damp-proof construction materials, enhancing methods to avoid the introduction of moisture during construction and creating the awareness on the health effect of dampness. These solutions are incomplete without the identification of behaviours that occupants require to manage dampness. Given that dampness is characterised by the availability of a source, a route for the moisture to travel and driving force for moisture movement, the occupants can be said to play a significant role in contributing to dampness. The paper aims to discuss these issues. Design/methodology/approach: As a result, this study seeks to examine the behaviours of occupants manifested to manage dampness in residential buildings. To achieve the aim, a qualitative research method was employed, under which interviews were carried out. Occupants in households in the northern and southern parts of England were interviewed to identify the actions, attitudes and beliefs in managing dampness. Findings: The findings revealed actions such as aeration and the use of anti-damp sprays. From the findings, dampness instilled attitudes such as anger, moodiness and unhappiness. In addition, dampness instilled cleaning habits in occupants due to the lack of comfort moulds create and the awareness of its health impact. Research limitations/implications: This research also contributes to existing debates on dampness reduction specifically in residential buildings. Originality/value: The identification of these behaviours creates the awareness for occupants on their roles in managing dampness and how dampness affects their behaviours in addition to the health impact.